Prognostic importance of myelosuppression during maintenance treatment of lymphoblastic leukaemia. Leukaemia in Childhood Working Party of the Medical Research Council. Issue 9 (September 1989) - Dolan, G; Lilleyman, J S; Richards, S M
Abstract : Children from the UKALL V trial were studied to assess the clinical importance of myelosuppression during uninterrupted 'maintenance' treatment of 'standard risk' lymphoblastic leukaemia. Those receiving daily 6-mercaptopurine and weekly methotrexate who were in first remission 20 months from diagnosis were divided into two groups on the basis of whether or not they had ever had an absolute neutrophil count of less than 0.5 x 10(9)/l recorded during maintenance treatment up to that time. Of 105 evaluable children, 45 (43%) became neutropenic at least once, and 60 (57%) did not. Seven (16%) of the neutropenic group subsequently relapsed compared with 27 (45%) of the remainder. This difference was still significant if the analysis was stratified by total treatment time (two or three years), age, sex, or diagnostic white cell count. Seven (16%) neutropenic children died in remission, compared with one (2%) of the non-neutropenic children. Therapeutic myelosuppression during standard maintenance treatment of 'standard risk' lymphoblastic leukaemia is associated with increased toxicity but a reduced risk of relapse. The unexplained improvement in long term survival in the United Kingdom in recent years may in large part be due to this.